Relativistic three-body model for final state interaction in D+ → K-π+π+ decay - Frederico, T.; Guimarães, K. S F F; De Paula, W.; Bediaga, I.; Dos Reis, A. C.; Magalhães, P. C.; Robillota, M.; Delfino, A.; Tomio, L. [UNESP] (My University, 2010)
A challenge in mesonic three-body decays of heavy mesons is to quantify the contribution of re-scattering between the final mesons. D decays have the unique feature that make them a key to light meson spectroscopy, in particular to access the Kn S-wave phase-shifts. We built a relativis-tic three-body model for the final state interaction in D+ → K -π+π+ decay based on the ladder approximation of the Bethe-Salpeter equation projected on the light-front. The decay amplitude is separated in a smooth term, given by the direct partonic decay amplitude, and a three-body fully interacting contribution, that is factorized in the standard two-meson resonant amplitude times a reduced complex amplitude that carries the effect of the three-body rescattering mechanism. The off-shell reduced amplitude is a solution of an inhomogeneous Faddeev type three-dimensional integral equation, that includes only isospin 1/2 K -π+ interaction in the S-wave channel. The elastic K-π+ scattering amplitude is parameterized according to the LASS data[1]. The integral equation is solved numerically and preliminary results are presented and compared to the experimental data from the E791 Collaboration[2, 3] and FOCUS Collaboration[4, 5].
Keywords: Bethe-Salpeter equation; Complex amplitude; Final state interactions; Ladder approximation; Meson spectroscopy; Rescattering mechanism; Resonant amplitude; Scattering amplitudes; Bosons; Hadrons; Integral equations; Scattering; Shear waves; High energy physics